Hydrocracking of Coconut Oil over Ni-Fe/HZSM-5 Catalyst to Produce Hydrocarbon Biofuel - Muhammad Al-Muttaqii; Firman Kurniawansyah; Danawati Hari Prajitno; Achmad Roesyadi (Indonesian Journal of Chemistry, 2019)
This present study was aimed to investigate the hydrocracking of coconut oil using Ni-Fe/HZSM-5 catalyst in a batch reactor at three reaction temperatures (350, 375, and 400 °C). The Ni-Fe/HZSM-5 catalyst was prepared by using incipient wetness impregnation. The Ni-Fe/HZSM-5 catalyst was characterized using XRD, BET, and SEM-EDX. From XRD results, the loading of Ni and Fe did not change the crystalline structure of HZSM-5 catalyst. The surface area of HZSM-5 was 425 m2/g and decreased after the addition of metals (Ni and Fe) into HZSM-5 support. These changes implied that Ni and Fe particles were successfully dispersed on the HZSM-5 surface and incorporated into HZSM-5 pore. The product of hydrocarbon biofuel was analyzed using GC-MS. The GC-MS results of hydrocarbon biofuel showed the highest compounds for n-paraffin and yield for gasoil was 39.24 and 18.4% at a temperature of 400 °C, respectively. The reaction temperature affected the yield and the composition of hydrocarbon biofuel. At this reaction temperature condition, decarboxylation and decarbonylation were favored; lead to the formation of n-alkanes with an odd number of carbon atoms chain length.